Strategies for relapse prevention among people with schizophrenia in KwaZulu-Natal Province, South Africa: Healthcare providers' perspectives. - Joyce Protas Mlay; Thirusha Naidu; Suvira Ramlall; Krushika Patankar; Khadija Israel; Laura Esquivel; Laura Curran; Sbusisiwe Sandra Mhlungu; Makhosazane Zondi; Richard Lessells; Andrew Tomita; Jennifer I Manuel (PLoS ONE)
Introduction Relapse is a significant challenge among people with schizophrenia and is broadly recognized by the aggravation of positive or negative symptoms, the need for re-hospitalization, more intensive case management, and/or changes in medication. The quality of inpatient care and proper transition to outpatient care are crucial in reducing the risk of relapse. Healthcare providers play vital roles in ensuring the continuity of care after patients are discharged from the hospital. Little is known about the roles of preventing relapse from the perspective of healthcare providers. This study explored the currently existing strategies for preventing relapse from the perspective of healthcare providers. Methods We captured the view of healthcare providers providing services to psychiatric patients using a qualitative methodological approach with descriptive phenomenology. We conducted audio-recorded, in-depth interviews with 15 consenting clinical providers from a public psychiatric hospital in Durban, South Africa. To facilitate analysis, we used Dedoose software (SocioCultural Research Consultants, LLC [www.dedoose.com]), and the themes were inducted from the data. Results Six major themes inducted from the analysis: Preparing patients and caregivers for discharge; Developing consistent and caring therapeutic relationships; Using an active approach to transition; Working with patients and caregivers concurrently; Creating and sustaining interagency connections; and Facilitating alternative forms of treatment. Conclusions Discharge planning and preparation are needed to ensure smooth transitions from hospital to outpatient care for relapse prevention. The healthcare system should ensure the availability of human resources for health at all levels of health facilities, and multidisciplinary teamwork will help a successful transition.